Efektifitas Core Stability Exercise terhadap Penurunan Nyeri Punggung Bawah Non Spesifik - Kartiko Pertiwi, Jasmine; Dwi Nur Astuti; Rustanti, Marti; Noerdjanah, Noerdjanah (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Non-specific low back pain is a health problem that is often experienced by many individuals, especially among workers, and can interfere with daily activities and productivity. Objective: This study aims to explore the effectiveness of Core Stability Exercise in reducing non-specific low back pain. Method: The method used was an experimental design with a pre test-post test control group approach, involving 30 subjects who experienced non-specific low back pain. Subjects were divided into two groups: a treatment group that received the Core Stability Exercise intervention, and a control group that only received education. The intervention was carried out 12 times with a frequency of 3 times a week for 4 weeks. Pain levels were measured using the QVAS scale before and after the intervention. Results: The results of the analysis showed that there was a significant reduction in the level of non-specific low back pain in the group that received the intervention compared to the control group. Conclusion: Core Stability Exercise has been proven to be effective in reducing non-specific low back pain. Keywords : Core Stability Exercise, Physiotherapy, Lower Back Pain